2002
DOI: 10.1074/jbc.m200797200
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Delivery of Connexin Genes to Human Breast Tumor Cells Inhibits in Vivo Tumor Growth by a Mechanism That Is Independent of Significant Gap Junctional Intercellular Communication

Abstract: The mechanism by which gap junction proteins, connexins, act as potent tumor suppressors remains poorly understood. In this study human breast tumor cells were found to exhibit diverse gap junction phenotypes including (a) undetectable Cx43 and no intercellular communication (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
165
2
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 39 publications
16
165
2
2
Order By: Relevance
“…The fs260-GFP construct was further mutated to substitute the putative endoplasmic reticulum FF motif, encoded within the aberrant 46 amino acids, to an AA motif (fs260-FF/AA) by using the forward primer 5Ј-C-GACAGAAACAAGCCGCCTTGCCGCAATTACAACAAGC-AAGCAAG, and reverse primer 5Ј-CTTGCTTGCTTGTTGTA-ATTGCGGCAAGGCGGCTTGTTTCTGTCG. All GFP-tagged variants were further cloned into the AP2 retroviral vector as described previously (25). Transient Transfection and Retroviral Infection-Cells were transfected with human Cx43-GFP, fs260-GFP, T259-GFP, or fs260-FF/AA-GFP by Lipofectamine 2000 (Invitrogen) as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…The fs260-GFP construct was further mutated to substitute the putative endoplasmic reticulum FF motif, encoded within the aberrant 46 amino acids, to an AA motif (fs260-FF/AA) by using the forward primer 5Ј-C-GACAGAAACAAGCCGCCTTGCCGCAATTACAACAAGC-AAGCAAG, and reverse primer 5Ј-CTTGCTTGCTTGTTGTA-ATTGCGGCAAGGCGGCTTGTTTCTGTCG. All GFP-tagged variants were further cloned into the AP2 retroviral vector as described previously (25). Transient Transfection and Retroviral Infection-Cells were transfected with human Cx43-GFP, fs260-GFP, T259-GFP, or fs260-FF/AA-GFP by Lipofectamine 2000 (Invitrogen) as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the mechanisms by which Cxs inhibit tumor growth were originally proposed to be through the diffusion of putative growth inhibitory factors via the Cx-modulated GJs (10). However, increasing evidence suggests that the GJ-independent roles are also involved in the Cx-induced growth inhibition (5,6,(11)(12)(13)(14). Further, it was reported that the C-terminal domain showed the same growth inhibition effects as the full-length Cx43 in certain cell lines (13,15) (and the present study).…”
Section: Discussionmentioning
confidence: 99%
“…Following transfection, replicationdefective retroviral supernatants were collected and filtered through a 0.45-m filter (Pall Gelman Laboratories, Ann Arbor, MI). BICR-M1R k cells expressing Cx43-GFP were engineered to stably express Panx1 and Panx3 by following a previously described protocol (30). Retrovirus encoding Panx1-GFP was also used to stably express GFP-tagged Panx1 in BICR-M1R k cells.…”
Section: Transfection and Engineering Of Stable Cell Lines-dsredtaggementioning
confidence: 99%